Systematic Review of the Effects of Iron on Cardiovascular, Kidney, and Safety Outcomes in Patients With CKD - Bernard Chan; Amanda Varghese; Sunil V. Badve; Roberto Pecoits-Filho; Murilo Guedes; Clare Arnott; Rebecca Kozor; Emma O’Lone; Min Jun; Sradha Kotwal; Geoffrey A. Block; Glenn M. Chertow; et al. (Kidney International Reports)
Introduction: Heart failure and chronic kidney disease (CKD) are closely associated, and iron deficiency is highly prevalent in both conditions. However, major cardiovascular and nephrology guidelines offer contrasting recommendations for iron use. We evaluated the effects of iron versus usual care or placebo on the clinical outcomes in patients with CKD. Methods: We conducted a systematic review and meta-analysis of randomized trials on i.v. or oral iron in patients with CKD (PROSPERO CRD42023453468). We searched Medline, Embase, and the Cochrane Register from database inception until February 1, 2024 to identify eligible trials. We determined the overall results and stratified them by dialysis- and nondialysis-requiring CKD using random effects models, with certainty of evidence assessed using the Grading of Recommendations Assessment, Development, and Evaluation approach. The primary composite endpoint was hospitalization for heart failure or cardiovascular death. Results: We identified 45 trials that met the inclusion criteria. Compared with usual care or placebo, iron reduced the risk of the primary composite endpoint (1659 events; risk ratio [RR]: 0.84, 95% confidence interval [CI]: 0.75–0.94; moderate certainty), an effect consistent across dialysis and nondialysis requiring CKD (P-heterogeneity = 0.70). The effect on the primary endpoint appeared driven by both components of hospitalization for heart failure (RR: 0.77; 95% CI: 0.61–0.96; moderate certainty) and cardiovascular death (RR: 0.81; 95% CI: 0.65–1.02; low certainty). The incidence of serious adverse events was lower for iron compared with usual care or placebo (RR: 0.90, 95% CI: 0.82–0.98; moderate certainty; P-heterogeneity = 0.09). Conclusion: Iron therapy may reduce the risk of heart failure and cardiovascular death in patients with CKD. Randomized trials evaluating the effects of iron on clinical outcomes are needed, especially in nondialysis patients with CKD with or without anemia.